Exploration and Innovation in Addressing Maternal, Infant and Neonatal Mortality - Khanal, L; Dawson, P; Silwal, R C; Sharma, J; KC, N P; Upreti, S R (Journal of Nepal Health Research Council, 2012)
The  Government  of  Nepal  has  been  remarkably  progressive  in  introducing  innovative  community-based maternal  newborn  and  child  health  interventions  in  an  effort  to  address  the  major  causes  of  maternal  and child  mortality  in  the  country. This  article  describes  the  introduction  of  innovative  interventions,  including  a review  of  the  landmark  research  that  precipitated  the  discussion  and  provided  evidence  of  practical  feasibility, the  acceptance  of  the  intervention  concept  and  validity,  the  approval  process  and  the  introduction  and  results from  the  pilot  interventions. These  interventions,  which  include  the  use  of misoprostol  to  prevent  post  partum haemorrhage  during  homebirths,  Morang  Innovative  Neonatal  Intervention,  gentamicin  in  Uniject  and  for  the management of neonatal  sepsis and newborn vitamin A  supplementation, are  in various  stages and demonstrate  the responsiveness of the Government to new approaches that address the major causes of maternal and child mortality. Keywords: chlorhexidine; gentamicin in Uniject; innovations; misoprostol; Morang Innovative Neonatal Intervention; Nepal; newborn vitamin A supplementation.